The feasibility and efficacy of a psychospiritual intervention with the insights from Bhagavad Gītā and Yin Yoga on a Turkish population: A mixed method approach - Akartuna, Duygu (Journal for the Study of Spirituality, 2025)
This pilot study examines the feasibility of a psychospiritual intervention integrating Bhagavad Gītā and Yin Yoga to reduce anxiety and enhance meaning in life and resilience among 20 Turkish women. Amidst challenges like COVID-19 and earthquakes, this novel approach, using quasi-experimental single-group mixed-methods pre-test/post-test design, aimed to assess the intervention’s adaptability and effectiveness within a cultural context unfamiliar with such methods. The online intervention used the Beck Anxiety Inventory, Meaning in Life Questionnaire, and Brief Resilience Scale and semi-structured interviews. SPSS was used for quantitative data analysis, and thematic analysis was applied to qualitative responses. Results showed a significant reduction in anxiety, with participants reporting improved coping strategies and a deeper sense of life’s meaning. While resilience scores showed only a slight, non-significant increase, qualitative feedback suggested subtle improvements in handling adversity. Additionally, the presence and search for meaning scores showed nuanced changes, with qualitative responses indicating a refined understanding of meaning in life post-intervention. This study underscores the value of mixed-methods research in psychospirituality, demonstrating the potential of integrating ancient spiritual teachings with modern psychological practices to support mental health and coping strategies in diverse cultural contexts.